Development Of a Polyherbal Formulation with Antioxidant and Hypoglycemic Properties for Diabetes Management - Sharma, Mukesh Chandra; Gupta, Seema; Bansal, Vijay Kumar; Gangwar, Atul Kumar; Deshpande, Mangirish; Kharche, Ajay; Suresh Dhumal, Jeevan; Gupta, Mahesh Kumar; Bhojak, Narendar (Journal of Neonatal Surgery, 2025)
The rising prevalence of diabetes mellitus has prompted extensive research into herbal remedies and their therapeutic potentials. This study aims to develop a polyherbal formulation combining various medicinal plants known for their antioxidant and hypoglycemic properties to enhance diabetes management. The selected herbs, including Momordica charantia, Trigonella foenum-graecum, and Cinnamomum verum, were identified based on their traditional use in lowering blood glucose levels and their ability to scavenge free radicals. The formulation was prepared using modern extraction techniques and evaluated for its phytochemical composition, antioxidant capacity, and antihyperglycemic effects in vitro using enzymatic assays. Preliminary findings indicate significant radical scavenging activities and promising hypoglycemic effects, aligning with existing literature on individual herbal components. The study underscores the synergistic benefits of combining selected herbs, potentially leading to improved glucose regulation and reduced oxidative stress in diabetic patients. This polyherbal formulation could serve as a novel therapeutic approach for managing diabetes, showcasing the importance of integrating traditional knowledge with contemporary scientific methods in developing effective health solutions. Further clinical trials are warranted to validate these findings.